Application of Hybrid Optimization Technique for Static Var Compensator Installation - D. Shahrulhisham, H.; H. Mansor, M.; Musirin, I.; Akoury, M.; Roslan, N.; A. Syed Mustaffa, S. (International Journal of Engineering and Technology, 2019)
Nowadays, the demand for electricity in power system network increased rapidly, influencing the expansion and urbanization of the network. This process results in inefficient system and may lead to unstable power system, high transmission line losses and many more. To alleviate these problems, Flexible Alternating Current Transmission System (FACTS) such as Static Var Compensator (SVC) can be used. An optimally-sized SVC must be placed at an optimal location. In order to find the optimal size of the SVC devices, a hybrid optimization technique called Immune Evolutionary Programming (IEP) is proposed in this paper. The proposed hybrid optimization technique was tested on the IEEE 26-Bus Reliability Test System (RTS) to minimize total voltage deviation index, to reduce transmission line losses and to improve voltage profile. The results of IEP have been compared with the two existing optimization techniques, which are Evolutionary Programming (EP) and Artificial Immune System (AIS). From this comparison, it is found that the proposed IEP method gives better optimization solution in terms of minimized transmission line losses, improved the voltage profile and reduced total voltage deviation compared to the other two techniques.Â Â